Muscular activity comparison between non-amputees and transfemoral amputees during normal transient-state walking speed. (September 2021) - Mehryar, Pouyan; Shourijeh, Mohammad S.; Rezaeian, Tahmineh; Khandan, Amin R.; Messenger, Neil; O'Connor, Rory; Farahmand, Farzam; Dehghani-Sanij, Abbas
Highlight: Individual muscle activity showed no significant differences in VL, SEM and TFL Similarities might be related to the unchanged neural strategy Dissimilarities might be related to differences in biomechanical demands Abstract: Research question: Would there be differences in muscle activation between healthy subjects' (HS) dominant leg and transfemoral amputees' (TFA) intact-leg/contralateral-limb (IL) during normal transient-state walking speed? Methods: The muscle activation patterns are obtained by calculating the linear envelope of the EMG signals for each group. The activation patterns/temporal changes are compared between-population using statistical parametric mapping (SPM). Results: Individual muscle activity showed significant differences in all muscles except vastus lateralis (VL), semitendinosus (SEM) and tensor fascia latae (TFL) activities. Significance: The information could be used by the therapists to prevent secondary physical conditions and prosthetic companies to improve the mobility of the amputees.